Analysis of the Increasing US-China Military Tension in the South China Sea and the Challenges for Indonesia - Erti Fadhilah Putri; Kukuh Setyo Pambudi; Agus Adriyanto (International Journal of Social Science and Religion (IJSSR), 2020)
Nowadays, the United States shows its foreign policy focus to the Asia Pacific region where there is a border conflict between China and the countries in the Southeast Asia Region. This paper tries to analyze the increasing tension of the US and Chinese military forces in the South China Sea and see how the challenges Indonesia will face with the escalation in the South China Sea. The United States of America began to increase its military power aimed to overseeing the South China Sea and Chinese Hegemony. The increase in US military strength certainly threatens China's interests in the South China Sea so that even in the middle of Covid-19, China is showing its military strength by conducting patrols and joint exercises in the waters of southern China. The improvement of the two superpowers can be seen in the framework of the Balancing Power theory, which emphasizes the analysis of military force tension in both countries. Whereas in analyzing the challenges faced by Indonesia, it can use the Balance of Threat theory. The purpose of this paper is to provide recommendations for the Indonesian government in dealing with the increasing tension in the South China Sea.